Relasi Kuasa Foulcout di Universitas Samudera Langsa - Masdalifah Sembiring (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
Despite applying Islamic sharia, the city of Langsa, through Universitas Samudera, was able to become a newmagnet for non-Muslim students as an educational destination in Aceh. On the other hand, as a minority, theirexistence needs to be explored. This study aims to describe the forms of tolerance accepted by non-Muslimstudents, describe the impact of tolerance on their daily lives, and describe the power relations between lecturersand non-Muslim students. This research took place from May to October 2019 and involved five non-Muslimstudents, two religious lecturers and a campus authority representative. This study uses a qualitative approachwith ethnographic types, and uses three methods of data collection, namely observation (fieldnotes), interviews(open-ended questions) and Focus Group Discussion (FGD) which are analyzed using reading, describing, andclassifying techniques. The results of this study indicate that there are several forms of tolerance accepted bynon-Muslim students, namely; the option to not take the semester exams and take grades from the church, thefreedom to work on assignments according to their perspectives and beliefs, and given the freedom to participatein discussions. Apart from the power of lecturers to carry out Islamization, religious lecturers carry out theirduties professionally. The effort of Islamization is carried out by providing a correct explanation of Islamaccompanied by evidence of its truth, not in striking and coercive ways.